Glycoconjugate secretion in human airways in vitro: effects of epithelium removal. Issue 1 (1998) - Sossé-Alaoui, H.; Labat, C.; Gorenne, I.; de Montpreville, V. Thomas; Bara, J.; Brink, C.
Abstract : The aim of this study was to examine glycoconjugate secretion in human airways with and without an epithelium. Glycoconjugate release in supernatants derived from human airways in vitro was determined using an ELISA assay with an anti-human mucin monoclonal antibody (MAb 3D3). This monoclonal antibody reacted strongly with Le b antigen but also recognized in vitro Le a and Le y determinents. In 11 of the 34 different lung samples (32%) studied the glycoconjugate levels were below the threshhold of detection for this assay. The mean basal secretion of glycoconjugates in human airways in vitro was 100 ±28 μg/g tissue (Period I;n = 23 different lung samples). The amount of glycoconjugate measured in the medium derived from human isolated bronchial ring preparations did not change under control conditions during the course of the experimental procedure (Period I; 128 ± 46 μg/g tissue and Period II; 159 ± 48 μg/g tissue;n = 13 paired lung samples). In the supernatants of airway preparations with an intact epithelium the amount of glycoconjugates detected was 90 ± 38 μg/g tissue (Period I;n = 12 different lung samples) and removal of the epithelium did not alter this basal glycoconjugate release (94 ± 60 μg/g tissue: Period I, n = 8 different lung samples). The absence of the epithelial layer was confirmed by histological evaluation. Methacholine (100 μM) induced a 10- and four-fold increase in glycoconjugate release from airways with and without an epithelium, respectively. In contrast, in preparations with an epithelium, LTD4 (10 μM) and anti-IgE (dilution: 1/1000) did not cause an increase of glycoconjugate release. The methacholine difference between airways with and without an epithelium was not significantly different( P > 0.10 ) . However, a treatment with atropine (100 μM) prevented the increase of glycoconjugate release in preparations with an epithelium. These data derived from a limited number of experiments suggest that the epithelium may not regulate the basal or stimulated release of glycoconjugates from isolated human airways.